ANALISIS PROSES PEMBELAJARAN TEKS PIDATO PERSUASIF KELAS IX SMP 05 SUTERA PESISIR SELATAN - Widia; Najmi Hayati; Dwi Mutia Chan (Ekasakti Educational Scientific Journal, 2024)
Education in Indonesia, including at SMP 05 Sutera Pesisir Selatan, has summarized the curriculum applied at all levels of education, including the 2013 Curriculum. Each lesson aims to develop students' cognitive, affective and psychomotor aspects. Affective, cognitive and psychomotor assessments are carried out through observation and analysis of the learning process, especially in learning persuasive speech texts. However, there are obstacles in the learning process, including students' difficulties in writing speech texts and the lack of variety and flexibility in the teaching methods used by teachers. The learning process only involves assessments at the beginning and end of learning, while the lack of variety and flexibility in teaching methods can hinder student creativity and independence. This research aims to analyze the process of learning persuasive speech texts at SMP 05 Sutera Pesisir Selatan using the 4C approach (Critical Thinking, Creative Communication, and Collaboration). Qualitative research methods were used with research instruments in the form of observation, interviews and documentation. The research results show that learning planning includes providing learning tools and the necessary hardware and software. The learning process consists of three stages: opening, core, and closing, which involve activities such as attendance, introduction to material, and group discussions. Evaluation of the learning process involves authentic assessment in the cognitive, affective and psychomotor domains, with assessment techniques such as written tests, observations and assignments.